Pengaruh Proses, Kualitas Layanan, dan Fasilitas terhadap Kinerja Ekspor Logistik Maritim Indonesia - Raja Ferry Surya Gemilang; Adenanthera Lesmana; Dhanan Abimanto (Logistics and Supply Chain Insights, 2025)
This study analyzes the influence of internal operational variables—Process, Service Quality, and Facilities—on the Export Performance of PT. Panah Perdana Logisindo, a freight forwarding company in Semarang. Maritime logistics plays a crucial role in national competitiveness, but company performance often faces challenges amidst the complexity of global supply chains . Employing a quantitative approach with a sample of 100 export service users, multiple linear regression analysis indicates that all three independent variables positively and significantly affect Export Performance (Y). The results reveal that Process has the most dominant influence (β=0.309), followed closely by Facilities (β=0.302) and Service Quality (β=0.255). The model explains 53.0% of the variance in the company's Export Performance (Raja Ferry, 2025 2). These findings confirm the necessity of strengthening micro-operational aspects (efficient procedures, robust networks, and staff professionalism) as a core strategy for enhancing profitability and customer loyalty amidst macro-logistical challenges in Indonesia.